Sea surface temperature evolution of the North Atlantic Ocean across the Eocene–Oligocene transition - K. K. Śliwińska; H. K. Coxall; D. K. Hutchinson; D. Liebrand; S. Schouten; A. M. de Boer (Climate of the Past, 2023)
A major step in the long-term Cenozoic evolution toward a glacially driven climate occurred at the Eocene–Oligocene transition (EOT), ∼34.44 to 33.65 million years ago (Ma). Evidence for high-latitude cooling and increased latitudinal temperature gradients across the EOT has been found in a range of marine and terrestrial environments. However, the timing and magnitude of temperature change in the North Atlantic remains highly unconstrained. Here, we use two independent organic geochemical palaeothermometers to reconstruct sea surface temperatures (SSTs) from the southern Labrador Sea (Ocean Drilling Program – ODP Site 647) across the EOT. The new SST records, now the most detailed for the North Atlantic through the 1 Myr leading up to the EOT onset, reveal a distinctive cooling step of ∼3 ∘ C (from 27 to 24 ∘ C), between 34.9 and 34.3 Ma, which is ∼500 kyr prior to Antarctic glaciation. This cooling step, when compared visually to other SST records, is asynchronous across Atlantic sites, signifying considerable spatiotemporal variability in regional SST evolution. However, overall, it fits within a phase of general SST cooling recorded across sites in the North Atlantic in the 5 Myr bracketing the EOT. Such cooling might be unexpected in light of proxy and modelling studies suggesting the start-up of the Atlantic Meridional Overturning Circulation (AMOC) before the EOT, which should warm the North Atlantic. Results of an EOT modelling study (GFDL CM2.1) help reconcile this, finding that a reduction in atmospheric CO 2 from 800 to 400 ppm may be enough to counter the warming from an AMOC start-up, here simulated through Arctic–Atlantic gateway closure. While the model simulations applied here are not yet in full equilibrium, and the experiments are idealised, the results, together with the proxy data, highlight the heterogeneity of basin-scale surface ocean responses to the EOT thermohaline changes, with sharp temperature contrasts expected across the northern North Atlantic as positions of the subtropical and ...